(untitled) (KMC Journal, 2025)
While the number of women leading schools has increased, they are more likely to achieve headship in small and basic schools rather than large and secondary schools. The asymmetrical representation of women in secondary school leadership is a pervasive phenomenon in the entire world. Despite having strong yearnings with required credentials, women are sidelined from the opportunity because of marginalizing policies and climate within schools. This study is undertaken to unveil the perception of female secondary school heads regarding the limited leadership opportunities for females in secondary schools in terms of policies, organizational culture, and socio-cultural aspects. Since the inquiry in such content remains less explored in the context of Nepal, this study is expected to fill the gap. This study employed an interpretive paradigm along with a qualitative approach. Key Informant Interview (KII) guidelines were used as tools for the collection of in-depth information. Fifteen female secondary school heads, having in-depth knowledge pertaining to the subject under investigation, from Chitwan district were selected purposively. The result displays that women school leaders have to grapple with impractical policies like maternity leave, head teacher selection, and secondary teacher selection; organizational culture such as extended and unscheduled work, lack of respect, and biased evaluation systems; and socio-cultural aspects as unequal distribution of domestic responsibilities, double burden, and cultural taboos. The study warrants gender sensitive policies and culture of the organization for the development of women school leaders. This exploration could provide insightful avenues for policy makers, educationists, educational institutions, and to all those who wish gender parity in school leadership.